Faktor Determinan Proses Persalinan Dengan Sectio Caesarea (SC) di Rumah Sakit Tk IV DKT Kota Kediri - Wiyatama Putri; Indah Rahmaningtyas; Susanti Pratamaningtyas; Dwi Estuning Rahayu (STIKES Karya Husada Kediri, 2026)
The number of cesarean section deliveries continues to increase at TK IV DKT Hospital in Kediri City. Cesarean sections carry a higher risk of complications compared to vaginal deliveries. This study aimed to analyze the determining factors that may influence cesarean section deliveries. The research used a quantitative method with a cross-sectional design and a retrospective approach. The total sample consisted of 444 mothers who gave birth, recorded in medical records for the year 2024, selected using total sampling. Data analysis was conducted using chi-square tests, contingency coefficient tests, and logistic regression on four medical indications: premature rupture of membranes (PROM), cephalopelvic disproportion (CPD), fetal distress, and abnormal fetal position. The results showed a significant overall relationship between the four factors and cesarean section deliveries (p=0.035), but with a weak correlation (R=0.186). Only abnormal fetal position had a significant effect on cesarean section deliveries (p=0.016), while the other factors showed no significant relationship. In conclusion, abnormal fetal position is the main determining factor influencing cesarean section deliveries. Therefore, early detection of fetal position and education for pregnant women are essential to ensure that cesarean sections are performed only for appropriate medical indications.